Sistem Pembangkit Listrik Hybrid Wind Turbine Sebagai Sumber Energi Wireless Sensor Network (WSN) - Suhairi, M; Hidayatturrahman, Hidayatturrahman (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
The availability of electrical resources is limited and replacing batteries for renewable energy sources such as solar is a complicated task and will increase costs. Therefore, a system was designed that utilizes wind and solar energy as a source of electricity. One alternative energy that is widely used is harvesting wind energy, and converting wind energy into electrical power. In this research, a wind power plant was designed using a horizontal wind turbine to harvest wind energy as an alternative energy source and the Covarage Awareness method was applied for Pekanbaru City. The power produced by the wind turbine for Pekanbaru City varies every day depending on the wind speed and the height of the building, but in this study the power produced was very small due to low wind speed conditions. Based on observations from Sunday, 18 December 2022 to Tuesday 27 December 2022, the average wind speed was low, namely 2 to 2.5 m/s, then on Wednesday, 28 December 2022 the average wind speed was moderate, namely 3.53 m/s , and finally on Thursday 29 December 2022 the wind speed decreased again, namely 2.71 in the low wind speed category. The comparison between the power obtained by the wind and the power obtained from the wind turbine in Pekanbaru City is 361.11 watts and the power that should be obtained by the wind turbine is 214.13 watts. However, based on observations, the power produced by the wind turbine at a wind speed of 8.17 m/s is 3 watts, because at this speed the wind turbine rotates for a short time of only 3 minutes. Therefore, the power produced by a wind turbine is very small.